Degradation potential of alkanes by diverse oil-degrading bacteria from deep-sea sediments of Haima cold seep areas, South China Sea - Lyu, Lina; Li, Jie; Chen, Yu; Mai, Zhimao; Wang, Lin; Li, Qiqi; Zhang, Si (Frontiers in Microbiology, 2022)
Marine oil spills are a significant concern worldwide, destroying the ecological environment and threatening the survival of marine life. Various oil-degrading bacteria have been widely reported in marine environments in response to marine oil pollution. However, little information is known about culturable oil-degrading bacteria in cold seep of the deep sea environments, which are rich in hydrocarbons. This study enriched five oil-degrading consortia from sediments collected from the Haima cold seep areas of the South China Sea. Parvibaculum, Erythrobacter, Acinetobacter, Alcanivorax, Pseudomonas, Marinobacter, Halomonas and Idiomarina were the dominant genera. Further results of bacterial growth and degradation ability tests indicated seven efficient alkane-degrading bacteria belonging to Acinetobacter, Alcanivorax, Kangiella, Limimaricola, Marinobacter, Flavobacterium and Paracoccus, whose degradation rates were higher in crude oil (70.3%-78.0%) than that in diesel oil (62.7%-66.3%). From the view of carbon chain length, alkane degradation rates were medium chains > long chains > short chains. In addition, Kangiella aquimarina F7, Acinetobacter venetianus F1, Limimaricola variabilis F8, Marinobacter nauticus J5, Flavobacterium sediminis N3 and Paracoccus sediminilitoris N6 were first identified as oil-degrading bacteria from deep-sea environments. This study will provide insight into the bacterial community structures, and oil-degrading bacterial diversity in the Haima cold seep areas, South China Sea, and offer bacterial resources to oil bioremediation applications.